Effect of Growth Regulators and Irradiation and Methyl Jasmonte in the Induction and Production of Flavonoids in Callus of Vitis Vinifera In-Vitro - Sarab, A. Almukhtar (Journal of Global Pharma Technology, 2018)
Plant tissue culture technology was used in the induction of callus from the node of the Vitis vinifera and thus stimulated to increase the production of flavonoids. The study was carried out in three stages after the sterilization of the explant: The first consisted of the establishment of callus cultivars by culturing the node on the MS medium, which is equipped with different concentrations and types of growth regulators. The second stage was performed by exposing the induced callus tissue to different doses of gamma radiation, while the third stage was performed by Cultivation the irradiated and unirradiated callus on the MS medium which was provided with different concentrations of methyl Jasmonate. The results of the study showed that auxien 2, 4-D had the highest wet and dry weight of (1817.20 and 94.38) mg respectively, while NAA achieved a wet and dry weight of (677.02 and 71.16) mg respectively, The concentration of 2.5 mg / L of auxien resulted in the highest rate of wet and dry weight of callus of (1991.75 and 124.75) mg, respectively. The irradiation treatment was significantly higher in the concentrations of Gintestnic, Rutin, Quercetin, Proanthocyanin, Nargnine, and Hesperdine of (133.08, 149.44, 157.82, 48.03, 89.42, and 72.75) and μg / g respectively were significantly higher than those obtained from the comparison treatment which achieved the lowest concentration rates. Keywords: Callus, flavonoids, grapes, methyl Jasmonte, irradiation.